020. A Preliminary Study of Post-Reconstructive Basal Cell Carcinoma Scars with Hyperbaric Oxygen Therapy Using Bates-Jensen Wound Assessment Tool Erick Latun1, Mendy Hatibie Oley2, Stevy Suoth2 - Latun, Erick; Oley, Mendy Hatibie; Suoth, Stevy (JBN (Jurnal Bedah Nasional), 2024)
Background : Non-melanoma skin cancer is 18-20 times more common among Caucasians and has a lower fatality rate. The study also indicated that women have more basal cell carcinoma than men. Treatments for basal cell carcinoma include surgery and on-surgical methods. Hyperbaric oxygen therapy is meant to speed up wound healing and prevent scarring. Through the use of the Bates-Jensen Wound Assesment Tool, basal cell carcinoma patients who undergo adjuvant hyperbaric oxygen therapy will be assessed in this study. Methods : The Bates-Jensen Wound Assessment Tool were used to collect data in this preliminary study. Participants who met the criteria were interviewed and given questionnaires to complete. According to the variable type, data is processed descriptively. Results : Six participants who fulfilled the inclusion criteria were interviewed about their Bates-Jensen Wound Assessment Tool showed to have good outcome with low score after the use of hyperbaric oxygen therapy. Conclusion: The Bates-Jensen Wound Assessment Tool is projected to be lower in severity in patients receiving hyperbaric oxygen therapy than in other control groups in this study.